Benefits of short-term modified stepping exercise on blood pressure and physical performance in female elderly with hypertension: a pilot study - Sarinukul, Chawin; Donpunha, Wanida; Nakmareong, Saowanee; Sawanyawisuth, Kittisak; Ruksapukdee, Wanida; Janyacharoen, Taweesak (Vol. 150, No. 6B (December 2021) pages 1703-1709.)
This study aimed to investigate the effects of continuous bench stepping on a 20-cm bench box in female elderly with hypertension. The participants were recruited in a rural area in Chum-Phae District, Khon Kaen, Thailand. - Title page.